Swimming economy: determinant factors and assessment issues - Giovanni Novaes; André Carneiro; Daniel Marinho; Victor Machado Reis; António Silva; Felipe Aidar (Universidade Federal de Santa Catarina, 2006)
Swimming economy is an important parameter in the control of the training process, since it has been demonstrated that this concept is related to the swimming performance. Swimming economy is affected by physiological and biomechanical constraints, therefore being a concept that reflects the swimmers´ adaptation to the liquid environment in those two domains. A review of the literature about swimming economy is presented, focusing some of the most relevant studies that have been conducted on this issue. Other than the biomechanical and physiological constraints, the swimming economy is influenced by other factors such as: swimming velocity, technical ability, training status, gender, age and anthropometric characteristics. Therefore a multitude of aspects are pertinent in the assessment of swimming economy and in the application of this concept in the control of the swimmers' training process. A proper assessment of the swimming economy requires the direct measurement of the oxygen uptake. The choice of the protocol to assess the swimming economy must be carefully done. Particular attention must be paid to the oxygen uptake kinetics across the different levels of exercise intensity. Therefore, both exercise intensity and duration are to be considered. The attainment of swimming velocities as close as possible to the competition velocity is also an important issue. Although few studies have measured directly the oxygen uptake of top-level performers during swimming, the literature shows that a discontinuous protocol, with increasing exercise bouts of duration between three and six minutes seem appropriate to assess the swimming economy. RESUMO Economia de nado é um parâmetro importante no controle do processo de treinamento, desde que foi demonstrado que este conceito é relacionado ao desempenho de nado. Economia de nado é afetada por aspectosfisiológicos e biomecânicos, sendo então um conceito que reflete a adaptação de nadadores ao ambiente líquido nesses dois domínios. Uma revisão da literatura sobre economia de nado é apresentada, focalizando alguns dos estudos mais pertinentes que foram publicados sobre este assunto. Diferente dos aspectos biomecânicos e fisiológicos, a economia de nado é influenciada através de outros fatores como: velocidade de nado, habilidade técnica, estado de treinamento, gênero, idade e características antropométricas. Então uma multidão de aspectos estão relacionados com a avaliação da economia de nado e na aplicação deste conceito no controle do processo de treinamento dos nadadores. Uma avaliação apropriada da economia de nado requer a medida direta da captação de oxigênio. A escolha do protocolo para avaliar a economia de nado deve ser feita cuidadosamente. Deve ser prestada atenção particular à cinética de captação de oxigênio pelos diferentes níveis de intensidade de exercício. Logo, a intensidade de exercício e duração devem ser consideradas. Em conseqüência a velocidade de nadar está relacionado intimamente com a velocidade de competição que também é um assunto importante. Embora poucos estudos medissem diretamente a captação de oxigênio de nadadores de alto nível durante a natação, a literatura tem demonstrado que um protocolo descontínuo, com turnos de exercício crescentes de duração entre três e seis minutos parecem apropriados para avaliar a economia de nado.